Dear Mr Carney … Memos to the new Bank of England governor. Issue 1 (7th June 2013) - Baker, Dean; Coppola, Frances; DeLong, Brad; Portes, Jonathan; Kaminska, Izabella; Corry, Dan; Pettifor, Ann; Allan, Tim; Banner, Bruce
Abstract : As Mark Carney prepares to take up the reins at the Bank of England, accompanied by sky‐high expectations for his economy‐saving powers, Juncture asked economists and commentators from Britain and abroad how they would advise the new governor.